MARKETING TOOLS FOR ENSURING THE FINANCIAL AND ECONOMIC SECURITY OF ENTERPRISES - TARASIUK, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2022)
In the conditions of a rapidly changing environment, uncertainty and the development of information technologies, the issue of ensuring the financial and economic security of enterprises is urgent and requires research. It is the marketing tools that provide the enterprise with the necessary specific information about the development of the market, necessary for making and justifying strategic and operational management decisions. Conducting marketing research is a necessary condition for the formation of information for the preparation of development strategies, action plans and ensuring the financial and economic security of enterprises. Because the use of marketing research methods and technologies allows forecasting of crisis phenomena in business and predicting possible risks. In turn, this will provide an opportunity to develop a set of measures, carry out localization and reduce negative consequences. The article examines the main aspects of ensuring the financial and economic security of enterprises in the rapidly changing environment and substantiates the feasibility of using marketing tools for monitoring, analysis and control of the internal and external environment of enterprises. It has been proven that the use of marketing tools in terms of ensuring financial and economic security is an integral component of the entire systemic management process. The functions of marketing to ensure financial and economic security were studied, modern digital marketing tools were considered. These tools should be adapted to modern conditions and the processes of globalization challenges and be used in the practical activities of enterprises.